A prospective cohort of patients with common scabies treated with 10% benzyl benzoate emulsion as monotherapy: EPIGALE study. (12th September 2021) - Caumes, Eric; Marty, Marc; Cadot, Michel; Boulanger, Patrick; Rousseaux, Chantal; Petit, Antoine
Abstract: Background: In addition to general measures, pharmacological treatment is the basis of the management of scabies. No recent data in real‐life are available on the efficacy and safety of 10% benzyl benzoate emulsion for skin application administered as monotherapy. Method: This prospective, multicenter, French observational study comprised a registry and a prospective cohort with a follow‐up at 28 days and a telephone call at week 12. To participate in the registry, patients had to be over 1 month old, ambulatory, presenting common, nonhyperkeratotic, untreated scabies. To be included in the cohort, patients had to be included in the registry and treated with two applications of 10% benzyl benzoate emulsion 8 days apart. The primary endpoint was cure at day 28. Results: Of the 186 patients included in the registry, 116 were included in the cohort. Fourteen patients were included in the cohort without being included in the registry, which led to a total of 130 patients in the cohort. At day 28, 119/130 (91.5%; 95% CI 85.4–95.6%) were clinically cured. The cure was confirmed by dermoscopy in 44/47 patients (93%). Among the 130 patients, the cure rate was 82% at week 12. Of the 119 patients cured at day 28, the rate of cure at week 12 was 89.9%. Conclusion: In real life, two applications of 10% benzyl benzoate emulsion 8 days apart provides high cure rates in patients with common scabies.